2011
DOI: 10.1183/09031936.00092411
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic thermal vapour ablation therapy in the management of heterogeneous emphysema

Abstract: The need for a less invasive procedure than surgical lung volume reduction that can produce consistent improvements with reduced morbidity remains a medical goal in patients with emphysema. We sought to determine the effect of bronchoscopic thermal vapour ablation (BTVA) on lung volumes and outcomes in patients with emphysema.44 patients with upper lobe-predominant emphysema were treated unilaterally with BTVA. Entry criteria included: age 40-75 yrs, forced expiratory volume in 1 s (FEV1) 15-45% predicted, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
125
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 24 publications
3
125
1
2
Order By: Relevance
“…A single-arm multicenter study of 44 patients with upper lobe emphysema indicated that patients receiving unilateral BTVA had an improved FEV 1 of 140.8 mL (p < 0.001) after 6 months, and 58% of patients had 12% improvement in their FEV 1 (69). However, the inflammatory reaction causes most patients to develop complications such as a fever, cough, sputum, and hemoptysis in the 4 weeks after the procedure; the inflammatory response gradually subsides after 12 weeks but it prolongs hospitalization.…”
Section: Btvamentioning
confidence: 99%
“…A single-arm multicenter study of 44 patients with upper lobe emphysema indicated that patients receiving unilateral BTVA had an improved FEV 1 of 140.8 mL (p < 0.001) after 6 months, and 58% of patients had 12% improvement in their FEV 1 (69). However, the inflammatory reaction causes most patients to develop complications such as a fever, cough, sputum, and hemoptysis in the 4 weeks after the procedure; the inflammatory response gradually subsides after 12 weeks but it prolongs hospitalization.…”
Section: Btvamentioning
confidence: 99%
“…The onset of effect is therefore delayed compared to the other ELVR procedures, with maximum effect not appearing until after 8 to 12 weeks. In two prospective uncontrolled studies, Snell et al (SGRQ) [30,31] reported therapeutic success similar to that achieved with EBV, specifically a volume reduction of the target area by up to 48 % and a significant improvement of lung function and quality of life (SGRQ) [30,31]. A typical post-interventional complication of BTVA is an overreaching inflammation accompanied by flu-like symptoms.…”
mentioning
confidence: 95%
“…Also in this issue of the ERJ are combined data from two studies using unilateral bronchoscopic thermal vapour ablation (BTVA) to achieve volume reduction [19]. SNELL et al [19] report outcomes for 44 patients with heterogeneous emphysema treated in two open-label studies (combined data set) with endobronchial application of steam.…”
mentioning
confidence: 99%
“…SNELL et al [19] report outcomes for 44 patients with heterogeneous emphysema treated in two open-label studies (combined data set) with endobronchial application of steam. The application of thermal energy leads to focal inflammation that progresses to fibrosis and contraction of lung tissue.…”
mentioning
confidence: 99%